A Surgical Management for Severe Rhinophyma With Five-Blade Scratcher. Issue 8 (November 2021) - Wang, Dong-Ming; He, Xu-Feng; He, Xiang; Zhang, Hui-Min
Abstract : Abstract: Rhinophyma, the final stage of acne rosacea, severely influences the patient's appearance and can only be treated by surgical methods. This case reports a simple, safe, effective, and economical surgical method-five-blade scratcher. After the surgical treatment, the overall nasal contour of the patient, a male with severe rosacea, was restored without scar formation. Thus, this surgical method reported in this case is feasible and easy to operate, and worthy of clinical promotion.